2014
DOI: 10.1136/annrheumdis-2014-205376
|View full text |Cite
|
Sign up to set email alerts
|

Frequent conversion of tuberculosis screening tests during anti-tumour necrosis factor therapy in patients with rheumatic diseases

Abstract: Approximately one third of patients with negative baseline TB screening develop conversion of at least one screening test during anti-TNF treatment. These findings should be considered when designing re-screening strategies and contemplating latent TB therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 25 publications
1
42
1
6
Order By: Relevance
“…In contrast to the result of no occurrence of TB observed in treated QFT-G converters in one Greek study [17], 7 (13%) of our untreated converters developed active TB. This discrepancy might be due to 1) the differences in the characteristics of the enrolled patients (with versus without INHP); and 2) the difference in the prevalence of active TB (49.4/100,000 Taiwan populations versus 5.0/100,000 Greece populations).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the result of no occurrence of TB observed in treated QFT-G converters in one Greek study [17], 7 (13%) of our untreated converters developed active TB. This discrepancy might be due to 1) the differences in the characteristics of the enrolled patients (with versus without INHP); and 2) the difference in the prevalence of active TB (49.4/100,000 Taiwan populations versus 5.0/100,000 Greece populations).…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to a recent study showing frequent conversion of LTBI screening tests in RA patients receiving biologic therapy [17,33], 28.9% of our RA patients had QFT-G conversion during one-year biologic therapy using follow-up IFN-γ≧0.35 IU/ml as the criteria. In contrast to the result of no occurrence of TB observed in treated QFT-G converters in one Greek study [17], 7 (13%) of our untreated converters developed active TB.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Because patients with RA may have false-negative IGRA or TST results due to immunosuppression, a negative IGRA or TST should not be interpreted as excluding the possibility that a patient has LTBI [89]. However, approximately one-third of patients with negative baseline TB screening develop conversion of TB screening during anti-TNF treatment [119]. So, if a patient with negative baseline TB screening develops active TB during biological therapy, two possibilities exist, either a false-negative IGRA or TST results or de novo TB infection.…”
Section: Preventionmentioning
confidence: 97%
“…Recent studies, however, have shown that TB conversions may occur during anti-TNF therapy in ~10% of RA patients. [24] It is unclear if these conversions always represent 'true conversions' . More data are needed to make recommendations regarding rescreening in the absence of definite TB exposure.…”
Section: Tuberculosismentioning
confidence: 99%